OSMOREGULATION IN THE SEA IN TELEOST FISHES - Nurmatova Rukhsora Utkir kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The development of the marine environment by vertebrates began at the end of the Silurian - the beginning of the Devonian and proceeded on the basis of the glomerular anlage characteristic of their ancestors. The tasks of osmoregulation in sea water are directly opposite to those in fresh water: in sea water, the osmotic pressure of the internal environment of the body is slightly lower than in sea water, and because of this, the body is constantly dehydrated. As a result, the filtration function of the kidneys, aimed at increasing water excretion, is weakened in marine bony fish. A significant part of the glomeruli does not participate in filtration at all.